2015
DOI: 10.1016/j.bbi.2015.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Stress sounds the alarmin: The role of the danger-associated molecular pattern HMGB1 in stress-induced neuroinflammatory priming

Abstract: High mobility group box-1 (HMGB1) is an endogenous danger signal or alarmin that mediates activation of the innate immune response including chemotaxis and pro-inflammatory cytokine release. HMGB1 has been implicated in the pathophysiology of several neuroinflammatory conditions including ischemia, traumatic brain injury, seizure and chronic ethanol use. In the present review, the unique structural and functional properties of HMGB1 will be explored including its affinity for multiple pattern recognition recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
143
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(145 citation statements)
references
References 63 publications
1
143
0
Order By: Relevance
“…Recently, it has been reported that psychological and/or acute intense stressor exposure in the absence of overt tissue damage can evoke a detectable local and systemic sterile inflammatory response and that DAMPs may have a (Fleshner, 2013;Frank et al, 2015b;Maslanik et al, 2013;Miller et al, 2015).…”
Section: Stress Damps and Sterile Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, it has been reported that psychological and/or acute intense stressor exposure in the absence of overt tissue damage can evoke a detectable local and systemic sterile inflammatory response and that DAMPs may have a (Fleshner, 2013;Frank et al, 2015b;Maslanik et al, 2013;Miller et al, 2015).…”
Section: Stress Damps and Sterile Inflammationmentioning
confidence: 99%
“…A number of studies have demonstrated that prior exposure to acute or chronic stressors potentiates the neuroinflammatory and microglial proinflammatory response to a subsequent immune challenge (Frank et al, 2015b). Interestingly, we found that intracisterna magna administration of an HMGB1 antagonist (box A) before stress exposure blocked the potentiated ............................................................................................................................................................. microglial proinflammatory response to an immune challenge ex vivo.…”
Section: Hmgb1mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies find both acute and chronic alcohol increase neuroimmune signaling in the brain (Vetreno and Crews, 2012; Walter and Crews, 2017). Acute stress also increases brain expression of cytokines such as TNF‐ α , IL‐1 β , and Ccl2 (Knapp et al., 2016) and the danger signaling molecule, high mobility group box‐1 protein (HMGB1) (Frank et al., 2015; Weber et al., 2015). Stress sensitizes neuroimmune responses (Frank et al., 2015), and stress hormones that are generally anti‐inflammatory have been hypothesized to have the opposite effect of enhancing brain innate immune signaling under some circumstances (Frank et al., 2015; Sorrells et al., 2009).…”
mentioning
confidence: 99%
“…Acute stress also increases brain expression of cytokines such as TNF‐ α , IL‐1 β , and Ccl2 (Knapp et al., 2016) and the danger signaling molecule, high mobility group box‐1 protein (HMGB1) (Frank et al., 2015; Weber et al., 2015). Stress sensitizes neuroimmune responses (Frank et al., 2015), and stress hormones that are generally anti‐inflammatory have been hypothesized to have the opposite effect of enhancing brain innate immune signaling under some circumstances (Frank et al., 2015; Sorrells et al., 2009). Further, studies in rats find partial restraint stress increases blood endotoxin and stress hormones, such as ACTH and corticosterone (CORT), as well as brain proinflammatory cytokines.…”
mentioning
confidence: 99%